Faktor yang Berhubungan MSDs dan Manajemen Risiko Metode JSA dan HAZOPs di CV Guna Agung: Factors Related to MSDs and Risk Management JSA and HAZOPs Methods at CV Guna Agung - Ummi Rahayu; Alfina Baharuddin; Ruslan Kalla (Program Pascasarjana Universitas Muslim Indonesia, 2022)
Background: Loading and unloading companies (PBM) have workers who rely on back power to carry goods needed by the company. Often this job poses a risk of back pain, one of which is complaints of Musculoskeletal Disorders. This is related to work patterns with fixed or restricted body positions, continuous repetition of movements, heavy loads, length of work, history of illness, and years of work. This study aims to analyze the factors associated with musculoskeletal disorders (MSDs) and risk management by using Job Safety Analysis (JSA) and Hazards Operability Study (HAZOPS) methods in CV. Use the Great Makassar. Method: This type of research uses an analytical observational method with a cross-sectional study design. The sampling method using total sampling was carried out on loading and unloading workers at CV. Guna Agung Makassar. In measuring workload, work shifts, work stress and work fatigue are measured using questionnaires. And for risk management using the Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOPs) methods. Result: There were 31 respondents involved in this study. Most of the respondents were in the age group 26-30 years (38.7%), the last education was high school/equivalent (61.2%), and 2-3 years of service (22.6%). The results of multivariate statistical tests showed that there was a relationship between years of service (p=0.003), length of work (p=0.007), disease history (p= 0.045), the weight of burden (p= 0.012), repetitive activities (p= 0.020), and work attitude (p= 0.050) with complaints of musculoskeletal disorders in workers at CV. Guna Agung Makassar. However, smoking habits (p= 0.125) had no relationship to complaints of musculoskeletal disorders in workers at CV. Guna Agung Makassar. For risk management using the JSA and HAZOPs methods, it is found that there are potential hazards associated with complaints of musculoskeletal disorders. Conclusion: Years of service, length of work, history of the disease, smoking habits, the weight of the burden, and repetitive activities have a significant relationship with complaints of musculoskeletal disorders in workers at CV. Guna Agung Makassar.